How Can We Prevent Pilgrims from Contracting Respiratory Infections During Pilgrimage? - Azmel, Azureen binti (International Journal of Human and Health Sciences (IJHHS), 2024)
The Hajj and Umrah mass gatherings attract millions of Muslim pilgrims to the Kingdom of Saudi Arabia each year. These events increase the risk of pneumococcal disease, especially among the large number of elderly pilgrims with co-morbidities. Many Hajj pilgrims arrive with risk factors for pneumococcal disease and worship under conditions that promote transmission, infection, and disease. A substantial proportion of Hajj pilgrims are older adults, with more than 50% aged >50 years and roughly 25% are at least 65 years. While pneumococcal vaccination is not officially part of the Hajj health requirements set by the Saudi authorities, many countries have recommendations to vaccinate their own at-risk populations and prospective pilgrims. The Scientific Committee for Influenza and Pneumococcal Vaccination of the Saudi Thoracic Society recommends the following before the Hajj season:1) All persons at ≥50 years are recommended to receive sequential vaccination before the Hajj or Umrah beginning with PCV13 followed by PPV23 at least 8 weeks later (ideally 1 year). If this is not possible, it is recommended to administer one dose of PPV23; 2) Immunocompetent persons <50 years with risk factors are recommended to receive a single dose of PPV23 at least 3 weeks before the Hajj; 3) Because of a lack of evidence, it is not recommended to provide pneumococcal vaccines routinely to healthy persons aged <50 years. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S8